2019
DOI: 10.3390/jcm8122051
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Nitric Oxide Signaling: Mechanisms and Therapeutic Implications

Abstract: In addition to their cholesterol-lowering effects, statins are associated with pleiotropic effects including improvements in heart failure (HF), reduced blood pressure, prevention of the rupture of atherosclerotic plaques and improved angiogenesis. In addition to these cardiovascular benefits, statins have been implicated in the treatment of neurological injuries, cancer, sepsis, and cirrhosis. These cholesterol-independent beneficial effects of statins are predominantly mediated through signaling pathways lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 107 publications
1
45
1
2
Order By: Relevance
“…Beyond lowering cholesterol, statins have been associated with a range of beneficial pleiotropic effects including anti-inflammatory, antioxidant and immunomodulatory effects, inhibition of platelet activation, regulation of pyroptosis, and increased plaque stability [12][13][14]. For example, statins mediate a dose-dependent decrease in C-reactive protein [15], may impact renal function [16,17], and attenuate postpartum cardiovascular dysfunction in a rat preeclampsia model [18].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond lowering cholesterol, statins have been associated with a range of beneficial pleiotropic effects including anti-inflammatory, antioxidant and immunomodulatory effects, inhibition of platelet activation, regulation of pyroptosis, and increased plaque stability [12][13][14]. For example, statins mediate a dose-dependent decrease in C-reactive protein [15], may impact renal function [16,17], and attenuate postpartum cardiovascular dysfunction in a rat preeclampsia model [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, intraperitoneally injected evodiamine increased eNOS, Akt, and CaMKII phosphorylation in WT, but not TRPV1 −/− mice. NO has long been known to promote neovascularization by stimulating both angiogenesis and vasculogenesis [136,[164][165][166]. Consistently, the Matrigel plug assay confirmed that evodiamine promoted angiogenesis in vivo, although neovascularization was prevented in TRPV1 −/− and eNOS-deficient (eNOS −/− ) mice [163].…”
Section: Chemical Stimulation Of Trpv1 Promotes Angiogenesis In a Camentioning
confidence: 62%
“…Multiple animal experimental and clinical studies have demonstrated favourable effects associated with nitrate supplementation-based boosting of the enterosalivary nitrate-nitrite-NO pathway, including reduced blood pressure, a cytoprotective effect against myocardial ischaemia-reperfusion injury, reversal of vascular dysfunction in older adults, cardiac protection through restoration of NO homeostasis, improved angiogenesis following chronic ischaemia, and an advantageous influence on cerebral vasospasm in subarachnoid haemorrhage [52][53][54][55][56][57][58][59]. Notably, the favourable cholesterol-independent effects of statins, such as reduced blood pressure, improved angiogenesis, and benefits in patients with heart failure, are realized through increased expression and function of endothelial NO synthases by a variety of mechanisms and pathways [60]. Hou et al demonstrated that homocysteine-induced endothelial dysfunction, a well-known risk factor in cardiovascular disease, is reversed by enhancing endothelial NO synthase [61].…”
Section: Role Of No In Biological Processesmentioning
confidence: 99%